Pemikiran Ekonomi Abu Yusuf - Siti Endang Sariniah; Luthfiah Mianda; Nazrah Athiyah; Muhammad Faathir Fy (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to examine the contribution of Abu Yusuf's thoughts in public financial governance and its relationship with the state financial system in Indonesia. In his famous work, Kitab al-Kharaj, Abu Yusuf revealed the principles of public economy based on Islamic values, such as justice in the distribution of wealth, transparency in tax management, and the responsibility of the state in ensuring the welfare of the people. This research approach is qualitative with a literature study method, utilizing classical and contemporary literature sources that discuss financial ideas according to Abu Yusuf and compare them with the Indonesian system. The analysis shows that Abu Yusuf's ideas, such as the proportional tax system (muqasamah), the prohibition of corruption in tax management (taqbil), and the state's responsibility in development, are still relevant to the principles of Indonesian public finance today. Therefore, his thoughts can be used as a normative reference in building a fair, open, and welfare-oriented state financial system.